Endothelial Mesenchymal Transition: Comparative Analysis of Different Induction Methods. Issue 1 (December 2016) - Pinto, Mariana; Covas, Dimas; Kashima, Simone; Rodrigues, Claudia
Abstract Background Endothelial-Mesenchymal-Transition (EndMT) plays an essential role in cardiovascular development, and recently became an attractive therapeutic target based on evidence supporting its involvement in fibrosis and cancer. Important questions that remain to be answered are related to the molecular mechanisms that control EndMT in different organs and distinct pathological conditions. The lack of a detailed protocol for induction of EndMT and the assumption that TGF-β isoforms play similar roles on different types of endothelial cells, limit progress in the field. The aim of this study was to compare the induction of EndMT by TGF-β isoforms in endothelial cells of different sources, and define a detailed protocol for EndMT assessment in vitro. Results We compared the dose-dependent effect of TGF-β isoforms, under normoxia and hypoxia, on the induction of EndMT in human coronary and pulmonary artery endothelial cells. Our results suggest that endothelial cells undergo spontaneous EndMT with time in culture under the conditions tested. The extent of EndMT induction by TGF-β was dependent on the dose and endothelial cell type. Furthermore, the potential of TGF-β to induce EndMT was reduced under hypoxia relative to normoxia. Conclusions Our work suggests that the response of endothelial cells to TGF-β is intrinsic to the dose, cell type and environment. Optimization of induction conditions may be essential, as pathways triggering EndMT may vary during development and pathological conditions. Therefore, caution is needed regarding indiscriminate use of TGF-β to induce EndMT for mechanistic studies.